PENGARUH NAA DAN BAP TERHADAP EKSPLAN PEGAGAN (Centella asiatica (L.) Urb.) - Heru Sudrajad; Didik Suharto; Fauzi . (Agrovigor, 2015)
Pegagan (Centella asiática (L.) Urb.) representing one of theplant which good of as drug. Plantof pegagan (Centella asiática (L.) Urb.) good of  to launch the urine, degrading blood pressure and quicken to heal the hurt. Ready of the seed for the crop of drug which require to be paid attention by quality from itself seed. One of the alternative to get the uniform seed and a flash in the pan is with the technique of tissue culture. Tissue culturelaboratory research was conducted Researchand Development Center for Medicinal Plantsand Traditional MedicineTawangmangu. Research Method use the Random Device of Complete Group at MS (Murashige Skoog) media with the treatment ofplant growth regulator the NAA concentration 0, 1, 3 and 5 mg / l and BAP concentration 0, 1, 2, 3 and 4 mg / l). Result of research show the combination of  giving of NAA 1 until 3 mg / l and BAP 1 until 5 mg / l of is condition of explan experience of the change become the callus. Treatment of combination NAA 3 mg / l and BAP 4 mg / l give the best result to callus forming with the quicker callus forming time that is 25 day. Keywords : Pegagan, Centella asiática (L.) Urb., tissue culture, NAA, BAP